Effects of Septum Resection for Secondary Infertility on Subsequent Reproductive Outcomes of in vitro Fertilization–Intracytoplasmic Sperm Injection - Chen, Huixiao; Sun, Ping; Zhang, Na; Lv, Shangge; Cao, Yongzhi; Yan, Lei (Frontiers in Medicine, 2022)
Objective To assess the effect of uterine septum resection on reproductive outcomes of in vitro fertilization (IVF) / intracytoplasmic sperm injection (ICSI) in patients with secondary infertility complicated with uterine septum. Methods A retrospective cohort study included 269 patients. Surgical group included 169 patients with secondary infertility complicated with uterine septum, who underwent 252 embryo-transfer (ET) cycles following septum resection. Control group consisted of 100 patients with secondary infertility and uterine septum, who underwent 178 ET cycles. Cumulative pregnancy rate and cumulative live birth rate after one complete assisted reproductive technology (ART) cycle were the primary outcomes. Results The results showed that the cumulative pregnancy rate was higher in the surgery group, and statistically significant difference was observed in the cumulative pregnancy rate between the two groups (71.0 vs. 59%, P = 0.044). In fresh ET cycle, no statistically significant difference between the two groups was evident (54.9 vs. 40.6%, P = 0.061). Statistical analysis of other results of the fresh ET cycle did not differ significantly between the two groups. In terms of frozen embryo transfer (FET) cycle outcomes, the clinical pregnancy rate and delivery rate in surgery group were 52.7 and 38.2%, respectively, which were significantly higher than those in the control group (38.2 and 22.5%, respectively) (P = 0.028 and P = 0.011). Conclusion The reproductive outcomes of IVF/ICSI after septum resection in patients with secondary infertility were better than that in the untreated group, suggesting that uterine septum resection can be performed in patients with uterine septum combined with infertility to improve their reproductive outcomes.